2021
DOI: 10.1101/2021.07.08.451631
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Positive selection and enhancer evolution shaped lifespan and body mass in great apes

Abstract: Within primates, the great apes are outliers both in terms of body size and lifespan, since they include the largest and longest-lived species in the order. Yet, the molecular bases underlying such features are poorly understood. Here, we leveraged an integrated approach to investigate multiple sources of molecular variation across primates, focusing on ~1,550 genes previously described as tumor suppressors, oncogenes, ageing genes in addition to a novel Build of the CellAge database of cell-senescence genes (… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 145 publications
(155 reference statements)
0
4
0
Order By: Relevance
“…Studies using elephant cell lines or tissues to measure the expression levels of the isoforms (qPCR) and knock-down assays (siRNAs) targeting combinations of the p53 isoforms, are highly anticipated to probe functional and physiological aspects, potentially contributing to the dissection/resolution of the Peto’s Paradox. In a broader view, such studies may also address the mechanisms whereby tumor suppressor genes and duplications regulate cellular senescence to drive lifespan and body mass ( Farre et al 2021 ; Tejada-Martinez et al 2022 ).…”
Section: Conclusion and Perspectivementioning
confidence: 99%
“…Studies using elephant cell lines or tissues to measure the expression levels of the isoforms (qPCR) and knock-down assays (siRNAs) targeting combinations of the p53 isoforms, are highly anticipated to probe functional and physiological aspects, potentially contributing to the dissection/resolution of the Peto’s Paradox. In a broader view, such studies may also address the mechanisms whereby tumor suppressor genes and duplications regulate cellular senescence to drive lifespan and body mass ( Farre et al 2021 ; Tejada-Martinez et al 2022 ).…”
Section: Conclusion and Perspectivementioning
confidence: 99%
“…While there is no doubt that ageing and longevity are in part genetically determined (Kenyon 2010), the pathways associated with ageing and longevity are incompletely known, both in terms of their constitutive genes/proteins and of their molecular 2 interactions. Indeed, genomic and transcriptomic analyses of organisms with high quality genomes, informed by careful considerations of molecular evolution, have uncovered sets of genes associated with ageing or longevity (Li and de Magalhães 2013;Gorbunova et al 2014;Keane et al 2015;Doherty and de Magalhães 2016;Foley et al 2018;Sahm et al 2018;Huang et al 2019;Toren et al 2020;Farré et al 2021;Irving et al 2021;Kacprzyk et al 2021;Kolora et al 2021;Orkin et al 2021;Lu et al 2022;Tejada-Martinez et al 2022) with little overlap, even across mammalian species (Farré et al 2021). This observation of a diversity of genetic bases of longevity and ageing across species is consistent with Darwinian theory, which predicts that longevity can be selected for, yet does not imply that homologous genes should be involved in longevity in different populations or species.…”
Section: Introductionmentioning
confidence: 59%
“…The authors also identified footprints of evolution related to SINE-Vntr-Alu (SVA) insertions and LTR transposons, reinforcing the importance of the action of these transposable elements in the evolution of great apes' gene-regulatory networks, especially in humans (Trizzino et al, 2017). The results of Tejada-Martinez et al (2022) show that the evolution of strategies for cancer resistance in the primate lineage is quite diverse, with modifications that can be found at the coding, expression, and regulatory levels, and that although the great apes lineage provides evidence of specific changes capable of giving greater longevity to the species of the group, the understanding of the relationship with cancer resistance is still developing for nonhuman species and needs to be further investigated.…”
Section: Great Apesmentioning
confidence: 83%
“…As in other mammalian lineages, the maximum life span and body mass are correlated in primates, and the great apes are the largest body size and long-lived species among them. Tejada-Martinez et al (2022) investigated the molecular evolution in coding genes and cis-regulatory sequences and gene expression evolution related to the development and maintenance of maximum lifespan and body size in the great apes and their association with pathways related to cancer suppression. They found only five genes with positive selection signals for the great ape lineage (IRF3, SCRN3, DIAPH2, GASK1B, and SELENO), all of which have functions related to cancer development and inflammatory responses.…”
Section: Great Apesmentioning
confidence: 99%